Planning research on rural integrated energy system based on coupled utilization of biomass-solar energy resources. (October 2022) - Wang, Yongli; Cai, Chengcong; Liu, Chen; Han, Xu; Zhou, Minhan
Abstract: Renewable energy such as solar energy and biomass energy in rural areas is very rich, but the energy utilization rate is low and the pollution is relatively serious. At present, it is urgent for rural areas to optimize, adjust and transform the energy consumption structure and find a more low-carbon and efficient way. The integrated energy system can improve the energy utilization rate and reduce the pollutant emission, and can effectively solve such problems encountered in rural energy development. Considering that rural areas are characterized by abundant energy resources and sufficient space resources, this paper proposes a rural-oriented integrated energy system planning method of coupling biomass and solar energy, effectively reducing the total annual cost and carbon emission and improving the comprehensive energy efficiency level. First, this paper analyzes the coupling mechanism of biomass and solar energy and proposes an integrated energy system optimization strategy based on rural scenarios. Secondly, a planning optimization model with the objective of optimal energy efficiency and economy and the lowest carbon emission is constructed. Finally, the improved differential whale optimization algorithm solves the problem, significantly improving solution efficiency. The stability of its optimization results has also been improved. The algorithm shows that the integrated energy system with coupled biomass and solar energy can save 40.34% and 28.09% of the total cost, reduce 80.33% and 67.27% of carbon emission, and increase 35.33% and 20.31% of energy efficiency than the integrated energy system with single allocation of biomass or solar energy resources, respectively.